2016
DOI: 10.1080/10253890.2016.1191465
|View full text |Cite
|
Sign up to set email alerts
|

Adulthood stress responses in rats are variably altered as a factor of adolescent stress exposure

Abstract: Stress exposure during development may influence adulthood stress response severity. The present study investigates persisting effects of two adolescent stressors upon adulthood response to predator exposure (PE). Rats were exposed to underwater trauma (UWT) or PE during adolescence, then to PE after reaching adulthood. Rats were then exposed to predator odor (PO) to test responses to predator cues alone. Behavioral and neuroendocrine assessments were conducted to determine acute effects of each stress experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Additionally, consistent with the current results, basic movements among non-stressed control subjects were unchanged across the ten trials. This effect appears to be consistent across development as significant decreases in basic movements relative to baseline performance were also observed among adolescent rats following exposure to either predator stress or underwater trauma stress [ 8 ]. Interestingly, treatment with a nociceptin/orphanin FQ (NOP) antagonist, which has shown potential use as an anxiolytic, mitigated the behavioral effects in stressed rats without affecting this measure in the non-stressed controls [ 27 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Additionally, consistent with the current results, basic movements among non-stressed control subjects were unchanged across the ten trials. This effect appears to be consistent across development as significant decreases in basic movements relative to baseline performance were also observed among adolescent rats following exposure to either predator stress or underwater trauma stress [ 8 ]. Interestingly, treatment with a nociceptin/orphanin FQ (NOP) antagonist, which has shown potential use as an anxiolytic, mitigated the behavioral effects in stressed rats without affecting this measure in the non-stressed controls [ 27 ].…”
Section: Discussionmentioning
confidence: 85%
“…The consistency of general performance measures suggests that they are robust outcome variables for detecting emotional behavioral responses to experimental manipulations over time. Our lab previously has shown that exposure to severe stress results in persistent decreases in basic movements on the EPM without changes observed in this measure among non-stressed controls [ 8 , 9 , 27 ]. Specifically, following predator stress, adult rats showed significant decreases in basic movements that were evident at 24-hours post-stress [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of stress in the lives of individuals (Moore et al, 2016) and specifically in the case of university students (Lapointe et al, 2018), and the role played by EI as well as self-efficacy in the said stress, few studies have simultaneously analyzed the role played by both aspects as regard stress (Aguilar et al, 2014). In response to this, the present research aims to determine the role played by self-efficacy and EI over perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…Gonadectomy at PND28, but not PND 70, erased these sex differences in MBP expression, suggesting the necessity of circulating estrogen in the development of myelin. Although organizational influences of hormones and the influence of sex chromosomes contribute to sex differences in myelin, evidence also suggests that activational effects of hormones play at least a partial role. Studies of female to male transsexuals provide unique insight into activation effects of hormones .…”
Section: Myelin Maturationmentioning
confidence: 99%